Upaya peningkatan kompetensi guru dalam membuat soal hots melalui kegiatan iht (in house trainning) di sd negeri wonowoso tahun pelajaran 2019/2020 - R D Astuti (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
Abstract.The objectives of this School Action Research are to: (1) increase teacher competence in making HOTS questions, (2) increase teacher involvement in joint activities through In House Training (IHT) (3) increase the insight and knowledge of Wonowoso Elementary School teachers in terms of understanding of the concept of HOTS questions. This research was conducted based on the fact that some of the teachers of SD Negeri Wonowoso Korwil II Surakarta City Education Office did not understand about the standard of assessment, especially in the preparation of HOTS questions. The form of this research is in the form of school action research using a cycle model. Each cycle used has several stages, namely the planning stage (planning), the implementation stage (acting), the observation stage (observation), and the reflection analysis stage (reflecting). As the population of this research, there are 9 teachers of SD Negeri Wonowoso. Data collection techniques of data variables through observation, documentation, interviews. Based on the results of the study, it can be concluded that there has been an increase in the performance of SD Negeri Wonowoso teachers in preparing HOTS questions after carrying out In House Training (IHT) activities.Keywords: Teacher Performance ,HOTS, In House Training (IHT)